Valorização de resíduos de Anacardiaceae: estratégia cromatográfica bioguiada para a obtenção de compostos bioativos (Anacardium occidentale e Mangifera indica) - Oiram Filho, Francisco (2024)
Secondary metabolites are compounds present in plants, have high biological activity, are present in fruits, but are also found in other parts of plants, such as bark, leaves and roots. Among these compounds, triterpenes and phenolics are classes that have proven bioactivity. Therefore, agro-industrial residues rich in these compounds can be a source of bioactive compounds, generating interest in the food and pharmaceutical industries. The objective of this work was to develop an extraction process and chromatographic methods for bioguided isolation of compounds in Anacardiacea (Anacardium occidentale and Mangífero indica) residues for the recovery of this residue. The extraction of compounds from the cashew stalk was carried out using bath ultrasound, using methanol as a solvent in 5 different samples (CCP09, CCP76, BRS275, BRS285 and EMBRAPA51). For the mango bark extract, solid-liquid extraction was carried out with immersion in ethanol for 96 hours at room temperature. For evaluation, quantification and isolation of compounds, chromatographic techniques were used on an analytical and preparative scale on C18 reversed-phase columns. A method validation was performed to quantify the compounds extracted from the cashew stalk. A fractionation of the extract from the mango bark was carried out in order to obtain biologically active fractions with anti-cancer activity, to then carry out bioguided isolation, aiming to isolate possible compounds with anti-cancer activity. A cytotoxic assay was carried out to evaluate the fractions from the mango bark extract. We evaluated 3 cancerous lines, PC3 (prostate), HCT-116 (colon carcinoma), SNB-19 (astrocytoma) and 1 healthy L929 (murine fibroblast). An analysis of column overload was also carried out using five injection loads (200, 400, 600, 800 and 1000 mg) in order to find a process execution limit. The results obtained for the extraction of anacardic acids from cashew were viable, providing total amounts that varied between 128.35 and 217.00 mg.100 g-1. The cytotoxic assay of the mango bark extract showed results for fractions F4, F5, F6 that inhibited 100 % of cell growth for all cells analyzed, F7 obtained 100 % inhibition for 3 cancer lines (SNB-19, HCT- 116 and PC3) and F8 inhibited 100 % of 2 cancer lines (HCT-116 and SNB-19). The column overload showed positive behavior in terms of load increase where the 800 mg load presented a good amount of mass, presenting favorable performance parameters. At the end of the processes, two classes of compounds were obtained through bioguided isolation, triterpenes and anacardic acids from fractions with anticancer activity. In conclusion, the cashew stalk proved to be an excellent source of anacardic acids, mainly monoene (15:1). Validation of the method was capable of reliably quantifying anacardic acids. The chromatographic strategies used were able to provide isolated compounds (triterpenes and anacardic acids) with anticancer potential from mango bark extract. Also defining the optimal process limit is an injection load of 800 mg of extract, with good productivity and low solvent consumption. Thus, showing the efficiency of the processes and valorization of these residual matrices.